Parameters estimation of vector-sensor array in colored noise based on quaternion-MUSIC - WANG Fei1; WANG Shu-xun2; ZHANG Kun-lei2 (Tongxin xuebao)
Parameters of vector-sensor array was estimated based on Hamilton quaternion. First,the theory and computa-tion method of right eigenvalue decomposition of Hamilton quaternion matrix was introduced in detail. Then,duplicate relation function （relation function of related function） of Hamilton quaternion was defined; it could not only express signal parameters but also restrain colored noise. Finally,Toeplitz matrix of duplicate relation function was constructed,and right eigenvalue decomposition was used to part signal subspace and noise subspace of this Toeplitz matrix. Signal parameters were estimated with quaternion-MUSIC method taking advantage of orthogonality between signal subspace and noise subspace. Some simulations illustrated the idea.